Pendampingan UMKM Dalam Pengelolaan Keuangan Dan Digital Marketing Pada Cemilan Pawon Reza Serta Seminar Tentang Tata Kelola Keuangan Berbasis Aplikasi Demi UMKM Profesional - Melly Saputri Danita; Dinda Sabriena; Restu Utomo; Faradina Aulia Jayanti (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The current period of Innovation Development (PI) at STIE Madani Balikpapan provides support to micro, small, and medium enterprises (UMKM) in the Sepinggan Subdistrict, Balikpapan City, who are members of the Prona Jaya group. The implementation involves students as the executors of Innovation Development, divided into several groups, with each group accompanying one UMKM entrepreneur. Our group assists the UMKM owner of Cemilan Pawon Reza in developing their marketing strategy by utilizing social media platforms such as WhatsApp and Instagram. Additionally, our group develops designs for product packaging and banners to enhance consumer appeal. In terms of simplifying financial reporting, we provide training to the owner of Cemilan Pawon Reza to use the Gyro Pos application, which can help them organize financial reports in a more orderly, easy, and secure manner.